Performance Appraisal of Tourism Sub Sector Companies In Indonesia Sharia Stock Index In the Period Of 2018-2020 - Maulana, Hartomi; Hastuti, Ely Windarti; Harahap, Soritua Ahmad Ramdhani; Imari, Iqbal; Salsabella, Oktavira Hanggreanda (El-Barka, 2022)
Introduction/Main Objectives: In financial statements, there is some data information needed to assess a company's financial performance. The study aimed to analyze the influence of financial performance assessments using EVA and MVA on abnormal returns of shares in tourism sub-sector companies listed in Indonesia Sharia Stock Index (ISSI) during the period 2018-2020. Background Problems: Although many previous studies have measured financial performance using the EVA and MVA methods, there is still limited use of EVA and MVA methods in tourism sector companies particularly listed in Islamic stock exchange. Novelty: The concept of economic value added (EVA) and market value added (MVA) become an alternative to performance measurement. Research Methods: This research is descriptive quantitative research with secondary data used as data collection technique. Dependent variable is abnormal stock return while independent variables used were EVA and MVA. Data was retrieved from Indonesian stock exchange web and 17 tourism sub-sector companies registered with ISSI during the period 2018-2020. Panel data regression with E-views tool employed as analysis technique. Finding/ Results: The study found that the coefficient sign for the EVA is positive and insignificant, while MVA is significant in affecting abnormal stock return. This indicates increasing in MVA will be causing increasing in abnormal return stock. Simultaneously, EVA & MVA have influence on abnormal stock return of the studied companies in Indonesia. The study suggests that investors can might consider MVA as an important factor in decision before purchasing their potential stock, also consider the importance of MVA impact on abnormal return as the basis of government’s related policy determinant.